Natality Detail File, 2010 (United States) ([Verlag nicht ermittelbar], 2016)
This collection provides information on live births in the United States during calendar year 2010. The natality data in these files are a component of the vital statistics collection effort maintained by the federal government. Birth data is limited to births occurring in the United States to United States residents and nonresidents. Births occurring to United States citizens outside of the United States are not included in this data collection. Dataset 1 contains data on births occurring within the United States, while dataset 2 contains data on births occurring in the United States territories of Puerto Rico, the Virgin Islands, Guam, American Samoa, and the Commonwealth of the Northern Mariana Islands. Variables describe the place of delivery, who was in attendance, and medical and health data such as the method of delivery, prenatal care, tobacco use during pregnancy, pregnancy history, medical risk factors, and infant health characteristics. Birth and fertility rates, and other statistics related to this study can be found in an Appendix to the User Guide under Detailed Technical Notes. Demographic variables include the child's sex and month and year of birth and the parents' ages, races, ethnicities, education levels, as well as the mother's marital status and residency status.